Hyponatremia upon presentation to the emergency department – the need for urgent neuroimaging studies - Arne Bokemeyer (Nature Portfolio, 2017)
Abstract This study aims to evaluate the necessity of urgent neuroimaging for emergency admissions exhibiting symptomatology of profound hyponatremia. We retrospectively analyzed the medical records of all patients admitted to the emergency room of the University Hospital Münster from 2010 to 2014 with a serum sodium value < 125 mmol/L. From 52918 emergency admissions, 261 patients with profound hyponatremia were identified, of whom 140 (54%) had neurological symptoms. Unspecific weakness and confusion were the most prevalent of these symptoms (59%). Focal neurological signs [FNS] were present in 31% of cases and neuroimaging was performed in 68% (95/140) of symptomatic patients. Multiple logistic regression analysis identified FNS, seizures, altered consciousness and age as independent predictors for conducting neuroimaging (all p < 0.05). Significant pathological findings consistent with acute symptomatology were evident in 17 cases, all of whom had FNS. Recursive partitioning analyses confirmed FNS as the best predictor of neuroimaging pathology (p < 0.001). Absence of FNS had a negative predictive value of 100% [95% confidence interval: 93–100%] for excluding neuroimaging pathology. In conclusion, emergency patients with profound hyponatremia frequently show nonspecific-neurological symptoms and may undergo neuroimaging unnecessarily. The lack of FNS may serve as a valuable criterion for withholding neuroimaging until hyponatremia has been corrected.